Effects of Δ⁹-tetrahydrocannabinol (THC), cannabidiol (CBD), and THC/CBD mixtures on fentanyl versus food choice in rhesus monkeys. (1st March 2023) - Carey, Lawrence M.; Maguire, David R.; France, Charles P.
Abstract: Introduction: There is considerable interest in utilizing cannabis-based products as adjuvants to opioid agonist therapies as phytocannabinoids like Δ 9 -tetrahydrocannabinol (THC) or synthetic cannabinoid receptor agonists appear to enhance the pain-relieving effects of opioids without enhancing problematic effects of opioids. Cannabis is a pharmacologically complex plant with hundreds of compounds, some of which may have interactive effects. Therefore, studying compounds like THC in isolation does not accurately reflect the clinical use of cannabis. Methods: This study examined the effects of THC and cannabidiol (CBD), the two most prominent compounds in cannabis, on the reinforcing effects of fentanyl in rhesus monkeys in a food versus drug choice procedure. Responding on one lever was reinforced by delivery of a sucrose pellet, and responding on another lever was reinforced by delivery of an i.v. infusion of fentanyl. In each monkey, the largest dose of fentanyl that produced less than 20 % drug choice and the smallest dose of fentanyl that produced more than 80% drug choice was determined. Effects of pretreatment with THC and CBD, alone and in mixtures, were then examined. Results: THC, CBD, and THC:CBD mixtures did not reliably enhance or diminish choice for fentanyl up to doses that suppressed responding in most monkeys, though some individual differences were observed, with THC and THC:CBD mixtures decreasing choice for large doses of fentanyl in one monkey and increasing choice for small doses of fentanyl in another. Conclusions: Phytocannabinoids like THC and CBD, administered alone or in mixtures, do not appear to reliably alter the reinforcing effects of opioids. Highlights: Cannabidiol did not increase, or decrease, the reinforcing effects of fentanyl. Δ 9 -tetrahydrocannabinol did not increase, or decrease, the reinforcing effects of fentanyl. Mixtures of these two did not increase, or decrease, the reinforcing effects of fentanyl. Cannabidiol and Δ 9 -tetrahydrocannabinol may be safe as adjuvants to opioid agonist therapies.